Descompusa in factori expresia :E= (3x-5)² - (2x+1)² este ?
Răspunsuri la întrebare
Răspuns de
14
E= (3x-5)² - (2x+1)²= [(3x-5) -(2x+1)][(3x-5)+(2x+1)]=
=(3x-5-2x-1)(3x-5+2x+1)=
=(x-6)(5x-4)
=(3x-5-2x-1)(3x-5+2x+1)=
=(x-6)(5x-4)
Răspuns de
3
E= (3x-5)^2 - (2x+1)^2= [(3x-5) -(2x+1)][(3x-5)+(2x+1)]=(3x-5-2x-1)(3x-5+2x+1)=(x-6)(5x-4)..... {DIFERENTA DE PATRATE: a^2-b^2=(a+b)(a-b)}
Alte întrebări interesante
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Geografie,
9 ani în urmă
Limba română,
10 ani în urmă
Matematică,
10 ani în urmă
Matematică,
10 ani în urmă